Let's review the steps in solving the equation \( 5(1 + 4h) + 2h = 27 \):
-
Original Equation: \[ 5(1 + 4h) + 2h = 27 \]
-
Expanding: \[ 5 \cdot 1 + 5 \cdot 4h + 2h = 27 \implies 5 + 20h + 2h = 27 \]
-
Combining Like Terms: \[ 5 + 22h = 27 \] (Here is where the mistake occurs; it incorrectly states \( 27h = 27 \), which is wrong.)
-
Solving for \( h \): Now, subtract 5 from both sides: \[ 22h = 27 - 5 \implies 22h = 22 \] Now, divide both sides by 22: \[ h = 1 \]
The mistake is in the step where it incorrectly states that after combining like terms, the equation becomes \( 27h = 27 \). The correct combination of terms leads to \( 22h = 22 \).